Pengaruh Penggunaan Media Komik Terhadap Minat Baca Siswa di SD 1 Menawan - Nihlatusshofi Ulwiyah; Khalimatus Sya'diah; Putri Wulan Puspitasari; Sekar Dwi Ardianti; Erik Aditia Ismaya (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
The aim of this research is to determine the effect of using comic media on students' reading interest at SD 1 Menawan. This research uses quantitative methods with the research method being Quasi Experiment (quasi experiment). Data collection techniques used in this research include interview guides, comics and questionnaires. The respondents in this study were all students in grades IV and V as the control and experimental classes at SD 1 Menawan. Data analysis techniques were processed and analyzed using SPSS 20 data processing software. The research data obtained was carried out by normality test, hypothesis test, and t-test. The sig value was obtained from the results of the t-test of the two variables of the experimental class and the control class of 0.000 < 0.05, it can be concluded that Ho was rejected, which means that the use of comic media as a teaching material has an effect on the increase in students' interest in reading at SD 1 Menawan.